Applying Justice Aspects as an Impact of Emergence of Judicial Review Decisions in Children's Cases Against the Law - A Wahid Ramdhan Dewanoto; Natangsa Surbakti (JUSTISI, 2024)
The study aims to describe the emergence of aspects of justice in juvenile crimes in decision number 131/PK/Pid.Sus/2015. This descriptive study uses a normative juridical approach. The data source is secondary data in the form of Judicial Review Decision Number 131/PK/Pid.Sus/2015 used library data collection methods, which were then analysed using qualitative methods with deductive logic. Based on the discussion carried out, it can be seen that the emergence of aspects of justice for children dealing with the law who are victims of wrongful arrest due to new evidence, so that the trial process from the beginning cannot bring up aspects of distributive justice by the state before the emergence of Judicial Review Decision Number 131/PK/Pid.Sus/2015, in which the panel of judges made mistakes in the first level process so that the justice that the child should have obtained is new. In addition, to provide distributive justice if there is a wrong arrest, new evidence that appears takes time.